Perioperative Adverse Outcome and Its Predictors After Emergency Laparotomy Among Sigmoid Volvulus Patients: Retrospective Follow-Up Study - Deresse T; Tesfahun E; Gebreegziabher ZA; Bogale M; Alemayehu D; Dessalegn M; Kifleyohans T; Eskandar G (Open Access Emergency Medicine, 2023)
Tilahun Deresse,1 Esubalew Tesfahun,2 Zenebe Abebe Gebreegziabher,2 Mandante Bogale,3 Dawit Alemayehu,3 Megbar Dessalegn,3 Tewodros Kifleyohans,1 George Eskandar4 1Department of Surgery, Debre Berhan University, Debre Berhan, Ethiopia; 2Department of Public Health, Debre Berhan University, Debre Berhan, Ethiopia; 3Department of Surgery, Debre Markos University, Debre Markos, Ethiopia; 4Department of Surgery, Glan Clwyd Hospital, Rhyl, UKCorrespondence: Tilahun Deresse, Department of Surgery, Debre Berhan University, Debre Berhan, Ethiopia, Email tmaed83@gmail.comBackground: Acute sigmoid volvulus is a surgical emergency with closed-loop obstruction of the colon that often requires emergency laparotomy, which is associated with a multitude of post-operative complications. Although sigmoid volvulus is the main cause of intestinal obstruction in Ethiopia, local studies of its management outcomes are limited.Objective: To assess the magnitude and predictors of adverse perioperative outcomes of emergency laparotomy for acute sigmoid volvulus in the Debre Markos Comprehensive Specialized Hospital (DMCSH), Amhara region, Ethiopia in 2023.Methods: This was a retrospective follow-up study. Descriptive statistics were used to measure perioperative outcomes and other study variables. Bivariable and multivariable logistic regression models were used to identify the predictors of adverse surgical outcomes. Associations were considered significant at p < 0.05 (95% confidence interval).Results: In total, 170 study participants were enrolled, with a response rate of 91.4%. Forty-nine patients (28.8%) developed perioperative adverse outcomes. Pneumonia (29 patients, 28.1%), surgical site infection (19 patients, 18.4%), and wound dehiscence (10 patients, 9.7%) were the most common complications. Pre-operative shock [AOR: 3.87 (95% CI: (1.22, 12.28))], pus or fecal matter contamination of the peritoneum [AOR: 4.43 (95% CI: (1.35, 14.47)], and a higher American Society of Anesthesiologists (ASA) score [AOR: 2.37 (95% CI: (1.05, 5.34))] were identified as predictors of perioperative adverse events.Conclusion: The perioperative adverse outcomes in this study were higher than those reported in Ethiopian national and global reports following emergency laparotomies. Hypotension at presentation, pus and/or fecal matter contamination of the peritoneum, and higher ASA scores are strong predictors of increased perioperative adverse outcomes. Therefore, healthcare providers and institutions involved in the delivery of emergency surgical care should emphasize the importance of early surgical intervention, adequate resuscitation, and patient monitoring to improve perioperative outcomes.Keywords: sigmoid volvulus, perioperative outcome, emergency laparotomy, Ethiopia